Longitudinal changes in response to a cycle-run field test of young male national "talent identification" and senior elite triathlon squads - Diaz, V.; Peinado, A. B.; Vleck, V. E.; Alvarez-Sánchez, M.; Benito, P. J.; Alves, F. B.; Calderón, F. J.; Zapico, A. G. (The Journal of Strength and Conditioning Research, 2012)
This study investigated the changes in cardiorespiratory response and running performance of 9 male "Talent Identification" (TID) and 6 male Senior Elite (SE) Spanish National Squad triathletes during a specific cycle-run (C-R) test. The TID and SE triathletes (initial age 15.2 ± 0.7 vs. 23.8 ± 5.6 years, p = 0.03; VO2max 77.0 ± 5.6 vs. 77.8 ± 3.6 ml/kg/min, nonsignificant) underwent 3 tests through the competitive period and the preparatory period, respectively, of 2 consecutive seasons: test 1 was an incremental cycle test to determine the ventilatory threshold (Thvent); test 2 (C-R) was 30-minute constant load cycling at the Thvent power output followed by a 3-km time-trial run; and test 3 (isolated control run [R]) was an isolated 3-km time-trial control run, in randomized counterbalanced order. In both seasons, the time required to complete the C-R 3-km run was greater than for R in TID (11:09 ± 00:24 vs. 10:45 ± 00:16 min:ss, p < 0.01 and 10:24 ± 00:22 vs. 10:04 ± 00:14, p = 0.006, for season 2005-2006 and 2006-2007, respectively) and SE (10:15 ± 00:19 vs. 09:45 ± 00:30, p < 0.001 and 09:51 ± 00:26 vs. 09:46 ± 00:06, p = 0.02 for season 2005-2006 and 2006-2007, respectively). Compared with the first season, the completion of the time-trial run was faster in the second season (6.6%, p < 0.01 and 6.4%, p < 0.01, for C-R and R tests, respectively) only in TID. Changes in post cycling run performance were accompanied by changes in pacing strategy, but there were only slight or nonsignificant changes in the cardiorespiratory response. Thus, the negative effect of cycling on performance may persist, independently of the period, over 2 consecutive seasons in TID and SE triathletes; however, improvements over time suggests that monitoring running pacing strategy after cycling may be a useful tool to control performance and training adaptations in TID.